1990
DOI: 10.1016/0033-5894(90)90074-u
|View full text |Cite
|
Sign up to set email alerts
|

Palynology of Oxygen Isotope Stage 6 and Substage 5e from the Cover Beds of a Marine Terrace, Taranaki, New Zealand

Abstract: Cover beds on uplifted Quaternary marine terraces in the Taranaki-Wanganui area of New Zealand include organic deposits which yield abundant pollen. In the west at Ohawe, marine shore platform deposits are overlain by laterally extensive lignites and laharic breccia, interbedded with alluvium and capped by tephra-rich loess. Following a time of presumably interglacial marine deposition on the platform, a long period of glacial climate is suggested by pollen floras dominated by grass and shrubland taxa. Trees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Nothofagus menziesii was present in the area during the LGM (e.g. Bussell, 1990), although forests in the South Taranaki lowlands were rare for much of the last glaciation (McGlone et al, 1984). There is, however, pollen evidence that Nothofagus menziesii was more abundant in the region about 4000 yr earlier than in the Waitotara Valley site (McGlone et al, 1984).…”
Section: Palaeoenvironmental Reconstructionmentioning
confidence: 85%
“…Nothofagus menziesii was present in the area during the LGM (e.g. Bussell, 1990), although forests in the South Taranaki lowlands were rare for much of the last glaciation (McGlone et al, 1984). There is, however, pollen evidence that Nothofagus menziesii was more abundant in the region about 4000 yr earlier than in the Waitotara Valley site (McGlone et al, 1984).…”
Section: Palaeoenvironmental Reconstructionmentioning
confidence: 85%
“…About Sm of section is exposed at the pollen site. Local stratigraphy and age constraints Palynology and radiocarbon dating at the Ohawe Beach Section, 5km southwest of Hawera (Head and Bussell, 1988;Bussell, 1990) (Fig. 1) together with mapping by Pillans (1990) have now confirmed the marine platform underlying the Ararata Road Site to be the Ngarino Terrace (Dickson et al, 1974), and not the Rapanui Terrace as indicated by previous mapping (e.g.…”
Section: Vegetationmentioning
confidence: 79%
“…Correlation of zone AR2 with oxygen isotope substage Se is also unlikely, because during the preceding glacial oxygen isotope stage 6, vegetation on the Taranaki lowlands would probably have been dominated by widespread grass-shrubland (Bussell, 1990), and no such record is evident in the Ararata Road Site.…”
Section: Age and Correlation Of The Ararata Road Sitementioning
confidence: 99%
See 2 more Smart Citations